Well-being and depression in individuals with subclinical hypothyroidism and thyroid autoimmunity—A general population study. (January 2015) - Fjaellegaard, Katrine; Kvetny, Jan; Allerup, Peter N.; Bech, Per; Ellervik, Christina
Abstract Background: The association between subclinical hypothyroidism (SCH), with and without raised thyroid peroxidase antibodies (anti-TPO), and well-being or depression is still controversial, in spite of many studies on the topic. Aims: In this large general population study of 8214 individuals, we aim to clarify the significance of elevated levels of anti-TPO as a marker of poor well-being and depression in euthyroid individuals and individuals with SCH. Methods: In participants from the Danish General Suburban Population Study (GESUS), serum thyroid stimulating hormone (TSH), total triiodothyronine (tT3), free thyroxine (fT4) and anti-TPO was measured. Prevalence of poor well-being and depression was measured using the WHO-5 Well-being questionnaire and WHO MDI [Major (ICD-10) Depression Inventory] questionnaire. Results: Raw score for well-being or depression overall and stratified for sex was not more significantly different in euthyroid individuals than in individuals with SCH, with or without high anti-TPO, except that euthyroid women with elevated anti-TPO had better well-being (P = 0.03) compared with euthyroid women with anti-TPO within the reference range. Conclusion: Elevated anti-TPO levels cannot be used as a general marker of poor well-being or depression in the general population.